2021
DOI: 10.3389/fpls.2021.650582
|View full text |Cite
|
Sign up to set email alerts
|

Coordinated and High-Level Expression of Biosynthetic Pathway Genes Is Responsible for the Production of a Major Floral Scent Compound Methyl Benzoate in Hedychium coronarium

Abstract: Methyl benzoate is a constituent of floral scent profile of many flowering plants. However, its biosynthesis, particularly in monocots, is scarcely reported. The monocot Hedychium coronarium is a popular ornamental plant in tropical and subtropical regions partly for its intense and inviting fragrance, which is mainly determined by methyl benzoate and monoterpenes. Interestingly, several related Hedychium species lack floral scent. Here, we studied the molecular mechanism of methyl benzoate biosynthesis in H. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 58 publications
2
22
0
Order By: Relevance
“…A total of 42 volatile compounds were identified, and terpenoids were the main volatile contents in six Hedychium accessions, which is in agreement with previous studies [ 7 , 8 , 10 ]. Furthermore, linalool and ( E )-β-ocimene constituted 62.34% of the total volatiles in ‘ZS’, which is in line with the previous findings that linalool and ( E )-β-ocimene are the main floral volatiles of this species [ 43 , 46 ]. The HCA analysis data showed that 42 volatile compounds from Hedychium accessions could be categorized into four clusters, while Spearman analysis revealed that these VOCs had different degrees of correlation ( Figure 2 ).…”
Section: Discussionsupporting
confidence: 90%
“…A total of 42 volatile compounds were identified, and terpenoids were the main volatile contents in six Hedychium accessions, which is in agreement with previous studies [ 7 , 8 , 10 ]. Furthermore, linalool and ( E )-β-ocimene constituted 62.34% of the total volatiles in ‘ZS’, which is in line with the previous findings that linalool and ( E )-β-ocimene are the main floral volatiles of this species [ 43 , 46 ]. The HCA analysis data showed that 42 volatile compounds from Hedychium accessions could be categorized into four clusters, while Spearman analysis revealed that these VOCs had different degrees of correlation ( Figure 2 ).…”
Section: Discussionsupporting
confidence: 90%
“…Hedychium coronarium J. Koenig, commonly known as ginger lily, is an important ornamental/medicinal plant that is widely grown in tropical and semitropical regions of the world. Terpenoids (monoterpenes and sesquiterpenes) and benzenoids/phenylpropanoids are the main volatile components of H. coronarium flowers, and they are released in abundant amounts during the blooming period, which is consistent with previous reports (Yue et al, 2014(Yue et al, , 2021Ke et al, 2019;Zhou et al, 2021). However, the molecular regulatory mechanism of melatonin underlying floral aroma production remains unknown.…”
Section: Discussionsupporting
confidence: 87%
“…The glass bottle was stilled for 30 min, and then a polydimethylsiloxane (50/30 µm divinylbenzene/carboxen) fiber (Supelco) was injected into the glass bottle to trap volatiles for 30 min. Thereafter, the adsorbed volatile compounds were analyzed using a GC-MS system with an Agilent 7890A GC and Agilent 5975C MSD as previously explained (Yue et al, 2015(Yue et al, , 2021.…”
Section: Headspace Volatile Collection and Gas Chromatography-mass Spectrometry Analysismentioning
confidence: 99%
“…Moreover, their expression pattern positively correlated with flower development as well as with the emission of monoterpenes, and their encoded enzymes localize to plastids ( Yue et al, 2015 ). Our functional characterization indicated that HcTPS3 functions in ( E )-β-ocimene production, HcTPS5 functions in linalool production, and HcBSMT2 functions in methyl benzoate production ( Yue et al, 2015 , 2021 ). Analysis of previously generated RNA-seq data showed that six HcMYB family members were clustered in a group involved in regulating secondary metabolism.…”
Section: Introductionmentioning
confidence: 89%